Traumatic Brain Injury Neurobiology, Diagnosis and Treatment - Zhou, Yongxia (IntechOpen, 2019)
Traumatic brain injury (TBI) is a significant public health problem. There are several advanced techniques available for the investigation of disease neurobiology, diagnosis, and treatment. This book covers many topics in the active TBI research field such as cumulative mild head injury review, brain changes, and risk factors, as well as post-concussion syndrome (PCS) definition, classification, and association with brain dysfunction. Brain changes, including blood flow, intracranial pressure, and neuroinflammation, the neurobiological basis of neuroprotective activation, as well as correlation with PCS, including sleep, are illustrated further. Furthermore, multiple biomarkers, including S-100?, UCH-L1, and GFAP for blood-brain barrier breakdown and neuronal injury, are reviewed thoroughly. Lastly, well-evaluated neuroprotective agents, hypothermia as a neuroprotective effect in TBI, and effects investigation, as well as sedation in TBI as a neurocritical and therapeutic strategy with different assessments, are reported. This book introduces readers to a number of perspectives, including TBI disease pathophysiology and post-concussion syndrome classification, associated brain changes, imaging diagnosis, and several useful biomarkers with high sensitivities, as well as multiple therapeutic strategies. Various advanced technical developments, upfront neuroimaging, and clinical data are presented together with comprehensive, up-to-date, and interesting examples. Detailed reviews and accurate illustrations together with objective and informative discussions of several challenging problems such as PCS and neuroprotective treatments are the advantages of this book. Finally, this book will hopefully convey the clinical aspects of TBI and help guide diagnosis and therapeutic research in this field.